Preparation and characterization of high radio-opaque E-glass fiber-reinforced composite with iodine containing methacrylate monomer. Issue 2 (February 2017) - He, Jingwei; Vallittu, Pekka K.; Lassila, Lippo V.
Abstract: Objective: The purpose of this study was to prepare radio-opaque E-glass fiber-reinforced composite (EFRC) with synthesized iodine containing methacrylate monomer. Methods: The synthesized iodine containing methacrylate monomer 2-hydroxy-3- methacryloyloxypropyl(2, 3, 5- triiodobenzoate) (HMTIB) was mixed with Bis-GMA and MMA in different mass ratio to prepare resin impregnating solution (RIS), and RIS without HMTIB was used as control. CQ and DMAEMA were added as photoinitiation system. E-glass fiber was thoroughly wetted by resin impregnating solution to prepare radio-opaque EFRC. Degree of double bond conversion (DC) was investigated by FT-IR analysis. Fiber volume fraction was analyzed by combustion and gravimetric analyzes. The Flexural strength (FS) and modulus (FM) of EFRC were measured using a three-point bending set up. Water sorption (WS) and solubility (SL) were measured until the mass variation of EFRC in distilled water kept stable. Radiographs were taken to determine the radiopacity of EFRC. Results: The FT-IR and 1 H NMR spectra of HMTIB revealed that it was the same as designed. ANOVA analysis revealed that increasing HMTIB concentration in RIS would decrease DC and increase fiber volume fraction. When compared with control EFRC, all of HMTIB containing EFRCs had higher or comparable FS and FM, no matter before or after water immersion. WS of EFRC decreased with increasing HMTIB concentration, while SL was nearly kept the same. Radiopacity of EFRC increased with increasing HMTIB concentration. Significance: The synthesized monomer HMTIB could be used to prepare EFRC with high radiopacity. Moreover, HMTIB containing EFRC would also have high mechanical properties and low WS.